Is AI Stirring Innovation or Chaos? Psychological Determinants of AI Fake News Exposure (AI-FNE) and Its Effects on Young Adults - Abdulgaffar Olawale Arikewuyo (Journalism and Media)
The rapid rise of fake news has become a growing concern in recent years; moreover, advancements in technology, particularly artificial intelligence (AI), have further exacerbated this issue by making it increasingly difficult to detect and verify fake news content. Also, the advent of AI, especially in auto-generated texts and deepfakes, has made identifying such misinformation significantly more challenging, as this may be associated with many predetermined factors. This study, therefore, investigated the psychological factors that influence media consumers’ belief in deepfakes and other AI-generated content, particularly focusing on how this type of news exposure impacts young adults. Using quantitative methodology, the study randomly sampled a total of (N = 381) young adults to explore the relationship between factors like low critical thinking, emotional attachment to news, and susceptibility to AI-generated fake news. The study found a critical linkage in the prediction that low critical thinking exacerbates exposure to AI-generated fake news content. This study validated the assumption that AI fake news exposure significantly predicts low media trust and antisocial behaviours. In addition, the study affirmed that emotional attachment to news will be positively associated with AI-FNE. This study ultimately concludes that factors such as low critical thinking and emotional attachment to news are predeterminants to AI-FNE, while AI-FNE further exacerbates antisocial behaviours and an individual’s belief in news platforms.